Oxidative stress in vertebrate semen: causes and consequences for male reproductive tactics - (:unkn) unknown (My University, 2025)
Oxidative stress (OS) is the result of random cellular damage caused by oxygen radicals that leads to cell death, ageing, or illness. OS has been identified as a major cause of infertility. In promiscuous species, the fertilizing ability of the ejaculate partly determines the reproductive success of males. Moreover, theory predicts that males with lower access to fertile females such as subdominant or sneaker males should be selected to invest more resources into enhancing their ejaculate quality. We therefore hypothesized that sub-dominant (in species with linear social hierarchy) or sneaker males (in species with alternative reproductive tactics) should prioritize antioxidant allocation to their sperm in order to protect their sperm from OS and thus produce higher quality sperm. We put this hypothesis to the test in a bird species in which social hierarchy correlates with mating success, and in a fruit bat which exhibits two alternative tactics, mate-guarding, harem males and sneaker males. In house sparrows, we found that ejaculate quality correlates with OS level in sperm, and that dominant males produce more oxidized and lower quality ejaculates. After experimentally manipulating the social environment, males matched their ejaculate quality to their new rank, while increases in antioxidant investment into ejaculates paralleled increases in ejaculate quality. Noticeably though, we also found that males at the bottom of the hierarchy were constrained in their resource allocation pattern and, contrary to theoretical expectations, were unable to produce high quality sperm with little oxidative damage. In the Seba's short-tailed bat, we also found that satellite males produced better sperm than harem males. However, when experimentally manipulated to acquire a new status - males switched harem/sneaker, sneaker/harem roles - males did not match the quality of their sperm to their new status. This suggests that reproductive tactics are either genetically determined or determined early in the life of individuals. This new project aims at addressing the new questions, which arose from our recent research. With this project we will investigate whether and how physiological constraints in resource acquisition and/or availability may affect resource allocation patterns and sperm quality under varying risks and intensity of sperm competition. We will also experimentally test whether energy as a whole or more specifically antioxidant resources constrain subordinate males in the house sparrow. Lastly, we will experimentally test whether increased antioxidant availability during early growth (from birth to weaning) determines reproductive tactics and antioxidant resource allocation patterns at adulthood in the Seba's short-tailed bat.
Keywords: Antioxidant defences; evolutionary trade-offs; house sparrows; oxidative damage; oxidative stress; reactive oxygen species; reproductive tactics; social status; sperm competition; sperm economics; sperm quality